New Records of Ferns from Northeastern Argentina and Uruguay - Meza Torres, Esteban Ismael (2010)
Is reported for the first time from ArgentinaDeparia petersenii (Kunze) M. Kato, Doryopteris collina (Raddi) J. Sm.; Ophioglossum reticulatum L. and Serpocaulon latipes (Langsd. & Fisch.) A.R.Sm. are reported for the first time from Uruguay. Serpocaulon catharinae (Langsd. & Fisch.) A. R. Sm is officially documented for the first time for Argentina and Uruguay.